Realization of ZIS Norms and Their Implementation at the National Zakat Amil Agency - Royani; Oyo Sunaryo Mukhlas; Atang Abdul Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This paper discusses the embodiment of Zakat, Infaq, and Sadaqah (ZIS) norms and their implementation at the National Amil Zakat Agency (BAZNAS). ZIS norms are the principles governing the collection, management and distribution of zakat, infaq and sadaqah in Muslim society. Implementing ZIS norms is important to ensure effectiveness and transparency in managing zakat funds. The method used in this study is a qualitative descriptive method using a descriptive analysis approach which aims to provide an overview of the structure of the data obtained. In conclusion, the embodiment of ZIS norms and their implementation at BAZNAS is very important to ensure effective, transparent and accountable zakat management. By complying with these norms, BAZNAS can carry out its duties properly and meet the community's expectations in channeling zakat funds to those entitled to receive them.